Studies in Gnosticism and Alexandrian Christianity - Broek, Roelof van den (Nag Hammadi and Manichaean Studies, 1996)
Preliminary Material -- Gnosticism and Hermetism in Antiquity: Two Roads to Salvation -- Eugnostus and Aristides on the Ineffable God -- Apuleius, Gnostics and Magicians on the Nature of God -- Autogenes and Adamas: -- The Creation of Adam's Psychic Body in the Apocryphon of John -- Von der jüdischen Weisheit zum gnostischen Erlöser: -- Jewish and Platonic Speculations in Early Alexandrian Theology: Eugnostus, Philo, Valentinus, Origen -- The Shape of Edem according to Justin the Gnostic -- Der Bericht des koptischen Kyrillos von Jerusalem über das Hebräerevangelium -- The Cathars: Medieval Gnostics? -- Juden und Christen in Alexandrien im 2. und 3. Jahrhundert -- The Christian "School" of Alexandria in the Second and Third Centuries -- The Authentikos Logos: A New Document of Christian Platonism -- The Theology of the Teachings of Silvanus -- The Teachings of Silvanus and the Greek Gnomic Tradition -- Index of Sources -- Nag Hammadi and Manichaean Studies.